Short communication. Estimation of cross-fertilization rate in saff lower (Carthamus tinctorius L.) - Velasco, L.; Fischer, M.; Fernandez-Martinez, J. M. (Spanish Journal of Agricultural Research, 2012)
Safflower is a promising oilseed crop for the production of specialty oils in the Mediterranean area. Oil quality traits such as high oleic acid content, high linoleic acid content, high saturated fatty acid content, or high gamma-tocopherol content have been developed in this crop. The traits are controlled by the genotype of the developing embryo and therefore they are influenced by the presence of foreign pollen. The objective of this research was to study the rate of cross-fertilization in safflower using the high oleic acid trait as a biochemical marker. An experiment in which each high oleic plant was surrounded by 24 low oleic acid plants was conducted over three environments in the same location at Córdoba, Spain. The average rate of cross-fertilization in the three environments was 5.7, 12.1, and 13.2%, though higher frequencies up to 35.9% were detected at the single-plant level and up to 58.3% at the single-head level. The low average outcrossing frequencies identified in this research indicate no need for large isolation distances between conventional cultivars and cultivars with special oil characteristics. However, the occurrence of a significant outcrossing rate should be taken into consideration if transgenic safflower is to be cultivated close to conventional safflower or in areas of distribution of wild Carthamus species.